The moderating effects of sex, age, and education on the outcome of combined cognitive training and transcranial electrical stimulation in older adults - Krebs, Christine; Peter, Jessica; Brill, Esther; Klöppel, Stefan; Brem, Anna-Katharine (Frontiers in Psychology, 2023)
Computerized cognitive training (CCT) has been shown to improve cognition in older adults via targeted exercises for single or multiple cognitive domains. Combining CCT with non-invasive brain stimulation is thought to be even more effective due to synergistic effects in the targeted brain areas and networks. However, little is known about the moderating effects of sex, age, and education on cognitive outcomes. Here, we investigated these factors in a randomized, double-blind study in which we administered CCT either combined with transcranial direct (tDCS), alternating (tACS) current stimulation or sham stimulation. 59 healthy older participants (mean age 71.7 "#6.1) received either tDCS (2 mA), tACS (5 Hz), or sham stimulation over the left dorsolateral prefrontal cortex during the first 20 minutes of a CCT (10 sessions, 50 min, twice weekly). Before and after the complete cognitive intervention, a neuropsychological assessment was performed, and the test scores were summarized in a composite score.Our results showed a significant three-way interaction between age, years of education, and stimulation technique (F(6,52) = 5.53, p = .007), indicating that the oldest participants with more years of education particularly benefitted from tDCS compared to the sham group, while in the tACS group the youngest participants with less years of education benefit more from the stimulation. These results emphasize the importance of further investigating and taking into account sex, age, and education as moderating factors in the development of individualized stimulation protocols.The study was registered on ClinicalTrials.gov (NCT03475446).